2013
DOI: 10.1111/1467-8268.12046
|View full text |Cite
|
Sign up to set email alerts
|

Relative Profitability of Cassava‐based Mixed Cropping Systems among Various Production Scale Operators in Ogun and Oyo States Southwest Nigeria

Abstract: Cassava is a very important crop in Nigeria by reason of its comparative production advantage over other staples.This study estimated the relative profitability of cassava producers and determined the effects of farm inputs on the level of profit of various scales of cassava producers in Ogun and Oyo States, Nigeria. Cross-sectional data were collected from 265 cassavabased farmers using a multistage sampling technique and were analysed using normalized profit function and budgetary analysis. Results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 15 publications
(16 reference statements)
3
17
0
1
Order By: Relevance
“…This was in line with the findings of Mutsears et al (1986) who indicated that mixed cropping is normally the predominant cropping pattern in Africa. Agwu and Anyaeche (2007) and Obayelu et al (2013) also observed that cassava is mainly cultivated as a mixed crop in Anambra and Ogun States of Nigeria, respectively. However, the finding is at variance with the findings of the Eze and Nwibo (2014) study in Delta State of Nigeria where mono-cropping production system was the most predominant.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This was in line with the findings of Mutsears et al (1986) who indicated that mixed cropping is normally the predominant cropping pattern in Africa. Agwu and Anyaeche (2007) and Obayelu et al (2013) also observed that cassava is mainly cultivated as a mixed crop in Anambra and Ogun States of Nigeria, respectively. However, the finding is at variance with the findings of the Eze and Nwibo (2014) study in Delta State of Nigeria where mono-cropping production system was the most predominant.…”
Section: Discussionmentioning
confidence: 97%
“…The farming population is aging with long years of farming experience, which is consistent with the findings of Yakasai (2010) among cassava farmers in Abuja, Nigeria. The high presence of smallholder farmers is characteristic of farm landholding in Nigeria (Obayelu et al 2013) owing to a low level of mechanization of traditional agriculture or land tenure problems. This has the potential to limit the types of varieties a farmer can plant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Farm Accountancy Data Network's structure of farms' income statements proposed by Argilés and Slof (2001, p. 376) shows that grants/subsidies increase the reported performance of FEs, which is measured using "gross farm income", "farm net value added" or "family farm income". According to Obayelu et al (2013), subventions enable various FEs to produce and sell their products at competitive market prices. Additionally, such grants allow farm(er)s to make long-term investments in new technologies such as wind turbines (Harsh et al, 2010) or irrigation projects (Fatah and Mat-Zin, 2013) that are necessary to address water and energy needs in production processes.…”
Section: Government Policies and Management Accounting Practices In Fmentioning
confidence: 99%
“…Production systems have been shown to develop mainly from different ecologies of production, extent of utilization of product, extent of market access, type of cropping system, as well as extent of diversification of production [2]. Within the cassava production system in Nigeria, distinct production systems have been identified by the type of mixed cropping pattern [3,4]. However, with respect to the analysis of cassava production systems on the basis of the extent of value addition and utilization of cassava biomass, there has been a dearth of information.…”
Section: Introductionmentioning
confidence: 99%